Physical oceanography during RV HEINCKE cruise HE614 - Tippenhauer, Sandra; Hoppmann, Mario; Wurl, Oliver (PANGAEA, 2023)
Conductivity-temperature-depth profiles were measured using a Seabird SBE 911plus CTD during RV HEINCKE cruise HE614. The CTD was equipped with duplicate sensors for temperature (SBE3plus), conductivity (SBE4) and oxygen (SBE43). Additional sensors such as a WET Labs C-Star transmissometer, a WET Labs ECO-AFL fluorometer and an altimeter (PSA-916 Teledyne (Benthos)) were mounted to the CTD. Temperature, conductivity and oxygen sensors are calibrated by the manufacturer once a year before being mounted in January. They are used throughout the year and no post-cruise or in-situ calibration is applied. All other sensors are calibrated irregularly. Data were connected to the station book of the specific cruise as available in the DSHIP database. Processing of the data including removal of obvious outliers followed the procedures described in CTD Processing Logbook of RV HEINCKE (hdl:10013/epic.47427). The processing report for this dataset is linked below.
Keywords: CTD; HE614; Heincke